History And Da'wah of Muhammadiyah in The Muslim Minority Area of Tana Toraja Regency - Risfaisal Risfaisal; Eliza Meiyani (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2022)
This research's main problem is finding out the history and movement of Muhammadiyah's da'wah in the Muslim Minority Area of Tana Toraja Regency. This study aimed to discover the historical aspects and strategies of Muhammadiyah's da'wah in the Muslim minority area of Tana Toraja district. The type of research conducted is descriptive qualitative research with the historiography method. Data collection techniques by observation, interviews, and documentation. The data analysis technique went through various stages: data reduction, data presentation, and conclusion drawing. In contrast, the data validity technique uses triangulation of sources, methods, and theories. The results of this study are the history of the birth of Muhammadiyah in Tana Toraja, founded in 1935 and brought by an activist of the Palopo branch of Muhammadiyah on behalf of Abdul Gani alias Wa' na or Wa' Ganing, with S. Machmud. Another research result is that the development of Muhammadiyah in Tana Toraja is very rapid, starting from the development of AUM, the growth of members, and religious activities. The da'wah strategy by Muhammadiyah is the da'wah method carried out by Muhammadiyah Tana Toraja, namely da'wah bil hal, da'wah bil oral, and also bil qalam.